2016
DOI: 10.1038/srep31989
|View full text |Cite
|
Sign up to set email alerts
|

Nest predation risk influences a cavity-nesting passerine during the post-hatching care period

Abstract: Some nest predators visually assess parental activities to locate a prey nest, whereas parents modify fitness-related traits to reduce the probability of nest predation, and/or nestlings fledge early to escape the risky nest environment. Here, we experimentally tested if the parental and fledging behaviours of oriental tits (Parus minor) that bred in the nest-box varied with cavity conditions associated with nest predation risk during the nestling period. The entrance of experimental nest-boxes was enlarged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
(71 reference statements)
0
9
1
Order By: Relevance
“…, Yoon et al . ). The length of the nesting period of Rockwren (44 days; Michelsen‐Heath ) is unusually long for a small passerine and also increases vulnerability to predation (Martin ).…”
Section: Discussionmentioning
confidence: 97%
“…, Yoon et al . ). The length of the nesting period of Rockwren (44 days; Michelsen‐Heath ) is unusually long for a small passerine and also increases vulnerability to predation (Martin ).…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have found that presence of a threat, such as a predator that is a danger throughout nesting, induces changes in the length of the nestling stage; presumably, an accelerated nestling stage decreases the time that undeveloped nestlings are at risk in the nest (Hua et al, ; Yoon et al, ). We found no evidence that the nestling stage was accelerated in the presence of house wrens, despite existence of variation in the length of the nestling stage.…”
Section: Discussionmentioning
confidence: 99%
“…Threats from predation can result in costly alterations in parental behavior throughout nesting (i.e., both egg and nestling stages) because general offspring predators are often relevant throughout the entire breeding attempt (e.g., Fontaine & Martin, ; Zanette, White, Allen, & Clinchy, ). In the presence of a threat, parents can alter behavior that results in reduced clutch size (Doligez & Clobert, ; Eggers, Griesser, Nystrand, & Ekman, ; Hua, Sieving, Fletcher, & Wright, ; Zanette et al, ), reduced clutch mass (Fontaine & Martin, ), changes in incubation behavior (Conway & Martin, ; Ferretti, Llambías, & Martin, ; Ibáñez‐Álamo & Soler, ; Massaro, Starling‐Windhof, Briskie, & Martin, ), and reduced nestling provisioning (Chalfoun & Martin, ; Dudeck, Clinchy, Allen, & Zanette, ; Fontaine & Martin, ; Pretelli, Isacch, & Cardoni, ; Sofaer, Sillett, Peluc, Morrison, & Ghalambor, ; Yoon, Kim, Joo, & Park, ; Zanette et al, ). Increased time off the nest during incubation results in eggs with decreased embryo mass, reduced residual yolk, and reduced growth efficiency (Olson, Vleck, & Vleck, ) and decreased nestling provisioning is associated with slower nestling growth and poorer quality nestlings (Scheuerlein & Gwinner, ; Thomson et al, ; Zanette et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations